Relationship between inter-pregnancy interval and risk of adverse maternal and neonatal outcomes in subsequent twin pregnancies - Ruowen Mu; Jie Wu; Danyang Yu; Zhangye Xu (BMC Pregnancy and Childbirth)
Abstract Background Inter-pregnancy interval (IPI), defined as the time span from one delivery to the next conception, is a controllable component of postpartum family planning. Studies show IPI affects adverse outcomes in singleton pregnancies, but its impact on twin pregnancies remains unclear. Our study aimed to explore the relationship between IPI and maternal and neonatal outcomes in subsequent twin pregnancies and also identified risk factors for these outcomes. Methods We conducted a retrospective cohort study of 583 women with twin pregnancies from 2016 to 2023. They were categorized into five groups based on IPI: <24 months, 24–35 months, 36–59 months, 60–119 months, and ≥ 120 months. Primary outcomes included preterm birth < 34 weeks, low birth weight/low birth weight, low birth weight/normal birth weight, and very low birth weight or extremely low birth weight in at least one twin. Secondary outcomes were postpartum hemorrhage and maternal hemorrhagic morbidity. Logistic regression analyses were conducted to investigate the relationship between IPI and adverse outcomes, as well as the risk factors for these outcomes. Results Women with an IPI of 36–59 months had a lower risk of very low birth weight or extremely low birth weight in at least one twin (aOR = 0.15, 95% CI = 0.03–0.81) compared to those with an IPI < 24 months. No relationship was found between IPI and other birth outcomes (P > 0.05). Modifiable risk factors including maternal body mass index at delivery, gestational weight gain, assisted reproductive technology, general anesthesia and anemia, along with unmodifiable risk factors including chorionicity, preterm premature rupture of membranes, gestational hypertension, preeclampsia, cesarean delivery history, placenta previa, low-lying placenta, and placental adherence, were related to adverse maternal and neonatal outcomes (P < 0.05). Conclusions An IPI of 36–59 months is a protective factor against very low birth weight or extremely low birth weight in at least one twin. No significant associations are found between IPI and other birth outcomes in women with subsequent twin pregnancies. Risk factors contributing to adverse perinatal outcomes should be considered.